Comparative Evaluation of Yeast Selenium and Sodium selenite Supplementation on Egg production and Egg Selenium Deposition in Layers - Dodamani, Pramod; Malathi, V. (Indian Journal of Animal Nutrition, 2023)
Selenium (Se) is an essential trace element, involved in many biological processes in animals, such as antioxidant defence, immune function, reproduction, and thyroid hormone metabolism. The effect of yeast selenium (SY) in laying hens’ production performance, egg quality, and selenium enrichment were evaluated in this experiment. Dual purpose Giriraja (180) were randomly divided into 4 groups having 5 replicates of 10 (9 females+1 male) birds each. The treatment groups included T1 (control diet without selenium), T2 (control diet + sodium selenite (SS) @ 0.5mg/kg diet), T3 (control + SS @ 0.3mg/ kg diet + SY @ 0.2mg/kg diet) and T4 (control diet+ SY @ 0.5mg/kg diet). The experiment was for 8 weeks starting from 30 weeks of age. 150 g feed per bird every day and 16h light schedule was followed. Egg production performance, egg quality parameters, and egg Se deposition were recorded. Supplementation of different sources of Se alone and their combination did not show significant difference in production performance viz., weekly hen housed egg production and Feed conversion ratio (FCR) per dozen eggs and also egg quality parameters. Significantly higher (P<0.05) egg selenium content was observed in the SY-supplemented group in the fourth and eighth weeks of the trial. Egg Se content did not differ significantly between the SS and combination supplemented groups in the fourth week, however, in the eighth week, the combination group’s egg Se content was significantly greater (P<0.05) than that of the SS supplemented group. In conclusion, the Se present in the feed raw material was sufficient to meet the requirement of layer (0.05-0.08mg/kg diet), further addition of Se was only useful to fortify the egg, which is supported by our results.